2016
DOI: 10.1002/clen.201500469
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Influence of Sesame and Green Gram Intercrops on Cotton in a Replacement Series

Abstract: Using a mixed culture replacement method, different plant species are planted with different densities per unit area. The benefits of using this method are evident; however, phytotoxic/competitive effects of these different plant species on each other are rarely studied, especially for cotton. Allelopathy is a biological phenomenon that can affect many aspects of plant ecology. A pot experiment was conducted to determine the individual and/or interactive effects of cotton, sesame, and green gram on each other.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…It has been found that at higher seed density of Carduus nutans the germination rate of Lolium perenne and Trifolium subterraneum diminished [7]. Similar results have been found in mixture crops when Sesamum indicum diminished the root length of Gossypium hirsutum [25], or when increasing plant number of Triticum aestivum diminished the biomass of Avena fatua [26]. Thus, different densities of the interacting plants may lead to different allelochemical concentrations, and therefore density should be taken into account when allelopathy experiments are performed [27].…”
Section: Introductionsupporting
confidence: 66%
“…It has been found that at higher seed density of Carduus nutans the germination rate of Lolium perenne and Trifolium subterraneum diminished [7]. Similar results have been found in mixture crops when Sesamum indicum diminished the root length of Gossypium hirsutum [25], or when increasing plant number of Triticum aestivum diminished the biomass of Avena fatua [26]. Thus, different densities of the interacting plants may lead to different allelochemical concentrations, and therefore density should be taken into account when allelopathy experiments are performed [27].…”
Section: Introductionsupporting
confidence: 66%
“…Weed management is a current necessity because weeds are widely distributed in agricultural systems and there is a yield loss of 9.7% as a result of 1,800 different types of weeds in agricultural crops per year. Management to reduce these weed species can be performed in different ways (Li & Wang, 2010;Shah et al, 2016;Shah et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Allelopathy is the concealment of one species by another because of poisonous chemicals; both negative and positive aspects are incorporated in this phenomenon (Kabir et al, 2010;Shah et al, 2016). Several researchers have reported weed species having inhibitory effects on weeds (Khalid et al, 2002;Javaid et al, 2005) while their negative effects on seed germination and seedlings growth of economically important crop plants have also been stated (Mulatu et al, 2009;Shah et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%